Influence of 24-Epibrassinolide on the Energetic Parameters and Early Stages of Growth and Development in Seedlings of Two Maize (Zea mays L.) Genotypes - Bojana Božilović; Bogdan Nikolić; Hadi Waisi; Jelena Trifković; Vladimir Dodevski; Bojan Janković; Sanja Krstić; Miloš Mojović (Agronomy, 2023)
Brassinosteroids (BRs) are a class of plant hormones that play important roles in regulating various physiological and developmental processes in plants. One of the most effective BRs involved in modulating crop growth is 24-epibrassinolide (24-EBL). The effects of different concentrations of 24-EBL on various biochemical and biophysical parameters critical to early growth stages and seedling development were investigated using two maize hybrids, ‘ZP 434’ (a new-generation hybrid) and ‘ZP 704’ (an older-generation hybrid). The evaluation of results is based on measurements of germination percentage, morphometric parameters, redox status, comparative analysis of thermodynamic parameters (such as Gibbs free energy, enthalpy, entropy), and the concentration of specific sugars in different parts of maize seedlings. The results indicate that the germination and initial growth of maize seedlings are influenced by the flow of crucial sugars from the remaining seed (as a source of nutrients) towards the plumule and radicle (as sink organs). Furthermore, alterations in Gibbs free energy play a significant role in these sugar transfers within the maize seedlings. The seed germination was most affected by the highest concentrations of 24-EBL, showing inhibitory effects, whereas lower and moderate concentrations of exogenously added 24-EBL exhibited a beneficial influence on the initial phases of seedling growth. The mentioned approach gives new insights into source–sink relationships and can be used as a quantitative measure of the germination energy, which until now has been a qualitative criterion in seed science.